Combustion Analysis of Ammonia/Gasoline Mixtures at Various Injection Timing Conditions in a High Compression Ratio SI Engine with Sub-Chamber - Mitsuhisa Ichiyanagi; Emir Yilmaz; Takashi Suzuki; Takanobu Okada; Hikaru Yamamoto; Masashi Kodaka; Hikaru Shiraishi; Shinnosuke Mukae; Ryota Tamba; Henry Widjaja; Leon Jonathan; Sebastian Gunawan; Gabriel Jeremy Gotama; Willyanto Anggono (Automotive Experiences, 2024)
Due to the problem of carbon dioxide (CO2) emissions, alternative fuels such as ammonia (NH3) have garnered a lot of attention lately. This is due to its carbon-free molecular structure, ease of transport, and high energy density. Unfortunately, ammonia is not without flaws since it is considered a difficult fuel to burn in conventional internal combustion engines. To further investigate the burning characteristics of ammonia, this study is conducted for ammonia/gasoline co-combustion using a modified engine equipped with a sub-chamber. The engine ran at 1000 RPM and had a 17.7 compression ratio with two injection timings of -55 and 10 crank angle degrees (Â°CA) after the top dead center (ATDC), while the ammonia energy ratios were adjusted across a range from 40% to 70%. The results show that the earlier injection timing allowed better premixing between the air and fuel mixture, thus enhancing the overall combustion characteristics. For the later injection timing, the nitrogen oxide (NOx) emissions decrease at the higher ammonia energy ratio due to the denitrification of the nitrogen oxides (DeNOX) process. Overall, the earlier injection timing appears optimal for the 40% to 70% ammonia energy ratio under the present condition.